EXPLORING THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN THE PARAGRAPH WRITING COURSE: STUDENTS’ PERCEPTIONS, USAGE, AND ATTITUDES - Maulidina, Alfina; Samtidar, Samtidar; Muhalim, Muhalim (JTechLP: Journal of Technology in Language Pedagogy, 2026)
This study investigates the use of Artificial Intelligence (AI) tools in the Paragraph Writing course among students of the English Language Education Study Program at Universitas Negeri Makassar. The research aims to explore students’ perceptions, usage patterns, and attitudes toward AI-based writing tools, particularly ChatGPT and QuillBot. Using a qualitative descriptive approach, data were collected through semi-structured interviews with four English Department students who reprogrammed the Paragraph Writing course during the 2024–2025 short semester. Thematic analysis revealed that students perceived AI as useful and easy to use, aligning with the constructs of the Technology Acceptance Model (TAM). Students used AI mainly for idea generation, grammar correction, and vocabulary enrichment. While they showed positive attitudes toward AI, they also expressed caution about dependency and ethical use. The findings imply that AI can effectively support writing instruction if guided by pedagogical supervision to ensure critical and ethical application in learning.